Sistem Pendukung Keputusan Berbasis Web untuk Penerimaan Bantuan Langsung Tunai Menggunakan Metode Multi Attribute Utility Theory (MAUT) di Desa Selemak - Irham Nabiza Trisna; Asbon Hendra Azhar (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
This study aims to develop a web-based decision support system to assist the selection process for Direct Cash Assistance (BLT) recipients in Selemak Village. The current manual selection process often leads to unfairness and subjectivity. This system was developed using the Multi-Attribute Utility Theory (MAUT) method, which is capable of providing selection results based on predetermined criteria and weighting. The research stages include collecting data on potential recipients, determining criteria, weighting, and implementing the system using PHP and MySQL. The system was evaluated using the K-Nearest Neighbor (KNN) algorithm to measure the accuracy of the calculation results. The results showed that the system was able to provide recipient recommendations with an accuracy of 96%, with 68 eligible families and 107 ineligible families. With this system, the process of determining BLT recipients is faster, more objective, and more transparent.